(untitled) (Cambridge, UK, 1995)
This book consists of 28 papers are from an international gathering in Saariselka, Finnish Lapland, in March 1992. The book describes the amazing successes of biological control of insects, plant pathogens, and weeds in agriculture and forestry with virtually no documented side effects, and the risks associated with introducing foreign or genetically altered organisms into an environment. It also covers the biological invasions that cause the problem, classical and augmentative biocontrol, the use of genetically modified organisms, and economics and registration.
Công nghệ sinh học trong bảo vệ thực vật,Tương tác giữa cây trồng và vi sinh vật,Tương tác giữa cây trồng và VSV
Keywords: Agricultural pests,Biological pest control agents,Dịch hại trong nông nghiệp,Tác nhân kiểm soát dịch hại sinh học; Biological control,Congresses,Congresses,Kiểm soát dinh học,Hội nghị hội thảo,Hội nghị hội thảo